2018
DOI: 10.1002/tesq.450
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Vocabulary Development in an EMI International School Context: Learners and Texts in EAL, Maths, and Science

Abstract: This article focuses on vocabulary in the context of English‐medium instruction at an international high school in Germany. Longitudinal testing was carried out using the Vocabulary Levels Test (VLT) (Nation, ; Schmitt, Schmitt, & Clapham, ), with 468 participants tested on entry to their first year of secondary school (Grade 6, aged 10–11 years old) and annually thereafter from 2009 to 2015. Learners with the lowest scores on the high frequency (first 2,000 level) words of the VLT in Grade 6 were nonnative sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 27 publications
7
35
1
1
Order By: Relevance
“…One aim of the study has been to assess receptive academic vocabulary knowledge among Norwegian upper secondary students. The average participant results in our study, 80.78%, are much higher than a previous study of Danish-speaking English L2 learners (38.52%) (Henriksen & Danelund, 2015), but lower than average results from students in a German EMI context (95.67% and 90.67%) (Coxhead & Boutorwick, 2018a). The higher scores from the German study could be expected due to student immersion in the English language across subjects.…”
Section: Mastery Of Academic Vocabularycontrasting
confidence: 79%
See 1 more Smart Citation
“…One aim of the study has been to assess receptive academic vocabulary knowledge among Norwegian upper secondary students. The average participant results in our study, 80.78%, are much higher than a previous study of Danish-speaking English L2 learners (38.52%) (Henriksen & Danelund, 2015), but lower than average results from students in a German EMI context (95.67% and 90.67%) (Coxhead & Boutorwick, 2018a). The higher scores from the German study could be expected due to student immersion in the English language across subjects.…”
Section: Mastery Of Academic Vocabularycontrasting
confidence: 79%
“…Previous research conducted in classroom settings for first-year upper secondary level students has used the VLT to show associations between vocabulary level knowledge and lexical demands in English language textbooks (Coxhead & Boutorwick, 2018a), as well as learners' written production (Henriksen & Danelund, 2015). The longitudinal study of German EMI students revealed that, on average, all of the non-native English-speaking learners first mastered the academic section of the VLT at the 86.7% mastery level in the 11 th grade (Coxhead & Boutorwick, 2018a) and the average participant did not reach the 96.7% mastery level recommended by . VLT test scores revealed that the lexical demands of textbooks could make reading comprehension challenging for many of these non-native English-speaking learners.…”
Section: Mastery Levels Of the Vltmentioning
confidence: 99%
“…Typically, EAL learners start their educational careers with significantly lower levels of vocabulary knowledge compared to their first language English (FLE) counterparts (NALDIC, 2015). Moreover, EAL learners also typically take longer to master the high-frequency vocabulary essential for academic success (Coxhead & Boutorwick, 2018). While previous research (e.g., August et al, 2005;Coxhead & Boutorwick, 2018) supports the assertion that EAL learners likely have less developed vocabularies than their FLE counterparts, what remains unclear is how such discrepancies impact their ability to function in English as a medium of instruction (EMI) classrooms.…”
Section: Introductionmentioning
confidence: 99%
“…In language learning, much work has been done for science, but not explicitly targeted at chemistry, and those that do exist have focused on ENL or ESL students (Johnstone and Selepeng, 2001). For EFL students, many studies have been done on language acquisition (Coxhead, 2018), but not for content knowledge acquisition in chemistry.…”
Section: Research Gap To Be Filledmentioning
confidence: 99%